The relationship of clinical and laboratory measurements to two different radiological scoring methods in ankylosing spondylitis - Ozgocmen, S; Ardicoglu, O; Kaya, A (Ios Press, 2000)
Two different methods for scoring the severity of radiological changes in 19 patients with ankylosing spondylitis, using plain X-rays of the lumbar spine and sacroiliac (SI) joints, were assessed in relation to clinical and laboratory measurements, Bath Ankylosing Spondylitis Radiology Index (BASRI) and Stoke Ankylosing Spondylitis Spine Score (SASSS) were used to evaluate radiologic changes. Disease activity was assessed using Bath Ankylosing Spondylitis Disease Activity Index (BASDAI). There was no correlation between duration of morning stiffness, night pain, laboratory variables (ESR, CRR hemoglobin, platelets) and any of the radiological scores. No significant correlation was found between BASDAI and both of the radiological scores. BASRI and SASSS correlated significantly with occiput-to-wall distance, Schober test, and finger-to-fibula distance, There was no significant correlation of radiologic scores with finger-to-floor distance and chest expansion. Right and left SI joint scores correlated significantly with BASRI and SASSS. The good correlation between spinal indexes and lack of correlation between clinical indicators of disease activity supports the notion that these two radiological scoring methods are measures of disease severity or deformity rather than disease activity. Radiological scoring methods are fundamental for the diagnosis and progression in AS and BASRI may be a more practical and appropriate method.
Keywords: ankylosing spondylitis; radiology; disease activity; BASRI; SASSS; spinal mobility